1987
DOI: 10.1007/bf00690890
|View full text |Cite
|
Sign up to set email alerts
|

Motor unit activity and surface electromyogram power spectrum during increasing force of contraction

Abstract: Twelve male subjects were tested to determine the relationship between motor unit (MU) activities and surface electromyogram (EMG) power spectral parameters with contractions increasing linearly from zero to 80% of maximal voluntary contraction (MVC). Intramuscular spike and surface EMG signals recorded simultaneously from biceps brachii were analyzed by means of a computer-aided intramuscular MU spike amplitude-frequency (ISAF) histogram and an EMG frequency power spectral analysis. All measurements were made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
173
4
9

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(203 citation statements)
references
References 21 publications
17
173
4
9
Order By: Relevance
“…Zipp 56 reported that the high-pass electrode filter characteristic compensates for the low-pass tissue filter characteristic, and then allowing improved observation of force induced spectral changes. A small interelectrode distance of less than 10 mm can produce the results which were dependent of force level 34 , while larger inter-electrode distances of equal or more than 20 mm can give the results which were independent of force 26,34,36 . However, in the present study an inter-electrode distance of 20 mm was used with a fix location of the surface electrodes over the muscle and the three relationship cases were found.…”
Section: Identification and Possible Causes For The Conflicting Resultsmentioning
confidence: 96%
“…Zipp 56 reported that the high-pass electrode filter characteristic compensates for the low-pass tissue filter characteristic, and then allowing improved observation of force induced spectral changes. A small interelectrode distance of less than 10 mm can produce the results which were dependent of force level 34 , while larger inter-electrode distances of equal or more than 20 mm can give the results which were independent of force 26,34,36 . However, in the present study an inter-electrode distance of 20 mm was used with a fix location of the surface electrodes over the muscle and the three relationship cases were found.…”
Section: Identification and Possible Causes For The Conflicting Resultsmentioning
confidence: 96%
“…This was thought to be due to the differences in the synchronization phenomena of the NMU by Buchthal and Handsen 1) , and to the ratio of innervation by the muscles and components of kinetic NMU-tonic NMU by Moritani and Muro 10) . With regard to the functional differences between the temporal and masseter muscles, it has been reported that recovery from muscular fatigue was faster in the temporal muscle and that the masseter muscle was more influenced by muscular fatigue 19) .…”
Section: Discussionmentioning
confidence: 99%
“…É possível analisar o sinal da EMG, tanto no domínio temporal como em frequência. No que se refere aos parâmetros da EMG no domínio do tempo, uma medida preconizada na literatura é a amplitude do sinal da EMG, chamada de Root Mean Square (RMS) 2 . Outros parâmetros, tais como amplitude da EMG integrada e envelope linear, também são utilizados para avaliar a ativação muscular 2 .…”
Section: Introductionunclassified
“…No que se refere aos parâmetros da EMG no domínio do tempo, uma medida preconizada na literatura é a amplitude do sinal da EMG, chamada de Root Mean Square (RMS) 2 . Outros parâmetros, tais como amplitude da EMG integrada e envelope linear, também são utilizados para avaliar a ativação muscular 2 . Em geral, a medida que a força aumenta, durante uma contração voluntá-ria isométrica máxima, a amplitude do sinal da EMG também aumenta, caracterizando então a relação EMG-força 1,2 .…”
Section: Introductionunclassified
See 1 more Smart Citation